Clinicopathologic Diversity of Undifferentiated Sarcoma With BCOR-CCNB3 Fusion: Analysis of 11 Cases With a Reappraisal of the Utility of Immunohistochemistry for BCOR and CCNB3. (December 2017) - Matsuyama, Atsuji; Shiba, Eisuke; Umekita, Yoshihisa; Nosaka, Kanae; Kamio, Takihiro; Yanai, Hiroyuki; Miyasaka, Chika; Watanabe, Reiko; Ito, Ichiro; Tamaki, Tomoko; Hayashi, Shinichi; Hisaoka, Masanori
Abstract : Undifferentiated sarcoma harboring the BCOR-CCNB3 fusion is characterized by its predilection to affect skeletons of adolescent males, cellular small round/spindle cell morphology, and CCNB3 immunoreactivity. We analyzed 11 cases of BCOR-CCNB3 sarcoma, 10 of which were identified in a reverse transcription-polymerase chain reaction–based screen of 85 patient samples recorded in our database as unclassified small round or spindle cell sarcomas. BCOR rearrangements were confirmed by fluorescence in situ hybridization in 8 tumors. All patients were males aged between 6 and 31 years. In addition to 5 tumors in soft tissue and 4 in the axial or appendicular skeletons, which are typical locations, a tumor was located in the paranasal sinus and another in the lung. Microscopically, the tumors comprised proliferating atypical spindle and/or small round cells with diverse morphologic features such as small concentric whorls, myxoid stroma, a hemangiopericytomatous appearance, and/or hyalinized collagen resembling a solitary fibrous tumor, and angiomatous or slit-like spaces containing extravasated erythrocytes. Tumor cells were immunoreactive to CCNB3 (9/11), BCOR (10/10), TLE1 (6/10), bcl-2 (9/11), CD99 (8/10), CD56 (8/10), c-kit (4/10), and cyclin D1 (10/10). In an immunohistochemical analysis of an additional 412 small round or spindle cell tumors, CCNB3 was detected in 6 (1.5%) and BCOR in 18 (4.4%). Our analysis highlights the varying clinicopathologic features of this tumor, which partially overlap with other small round or spindle cell tumors, including solitary fibrous tumor and vascular tumors. Because CCNB3 and BCOR immunohistochemistry lacks adequate sensitivity and specificity, a molecular genetic approach remains essential for diagnosis.